The impact of missing data on estimating HIV/AIDS prevalence and incidence in demographic sentinel survey studies - Mosha, Neema Ramadhani (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.